Play Based Literacy Programme Builds Early Childhood Language Foundations: Program Literasi Berbasis Bermain Membangun Dasar Bahasa pada Masa Kanak-kanak Awal - Yuni Emma Wati; Choirun Nisak Aulina (Academia Open, 2025)
General Background Early childhood literacy is a fundamental domain of development that supports children’s readiness for formal schooling and lifelong learning. Specific Background In Indonesia, concerns over low reading interest highlight the need for engaging literacy initiatives within early childhood education settings, particularly those grounded in developmentally appropriate practices. Knowledge Gap Despite the emergence of school-based literacy movements, limited qualitative evidence exists regarding how structured, play-based programmes operate in practice and how they relate to children’s observable literacy achievements. Aims This study analyzes the implementation of the GALERIA programme (Gerakan Literasi Bhayangkari Ceria) and examines the literacy skills of children aged 5–6 years at Kemala Bhayangkari 83 Sidoarjo Kindergarten. Results Using observations, interviews, and documentation, the findings show that regular activities—storytelling with puppets, personal storytelling, word-guessing games, shared reading, and role-play—stimulated three key domains: language comprehension, language expression, and emergent literacy, with most children demonstrating high achievement across these indicators. Novelty The study documents a school-initiated, participatory literacy movement structured around weekly peak events and daily classroom practices, offering a contextualized model of play-based literacy programming. Implications The programme provides a practical framework for cultivating early literacy culture in kindergartens and may inform similar initiatives in other early childhood institutions seeking developmentally appropriate literacy practices.Highlights: Weekly storytelling and interactive games supported strong comprehension of narratives and instructions. Children demonstrated confident verbal communication, including retelling stories and creating simple books. Visual word cards and picture books enabled recognition of letters, sounds, and basic writing skills. Keywords: Early Childhood Literacy; Play Based Learning; Emergent Literacy; Kindergarten Education; Language Development